2018
DOI: 10.1038/s41386-018-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of trace amine-associated receptor 1 in nicotine’s behavioral and neurochemical effects

Abstract: Nicotine addiction and abuse remains a global health issue. To date, the fundamental neurobiological mechanism of nicotine addiction remains incompletely understood. Trace amine-associated receptor 1 (TAAR1) is thought to directly modulate dopaminergic system and are thought to be a neural substrate underlying addictive-like behaviors. We aimed to investigate the role of TAAR1 in nicotine addictive-like behaviors. TAAR1 expression after nicotine treatment was evaluated by western blotting. c-Fos immunofluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 48 publications
6
43
0
Order By: Relevance
“…Studies from our lab and others have shown that TAAR1 agonists were effective to attenuate the behavioral and biochemical effects of stimulants such as cocaine and amphetamines [52]. Our recent study also demonstrated that activation of TAAR1 was effective to reduce nicotine-induced dopamine release and neural activation in the NAc [55]. Furthermore, TAAR1 agonists attenuated several kinds of nicotine-related behaviors, e.g., nicotine-induced behavioral sensitization, nicotine discrimination, nicotine self-administration, and reinstatement of nicotine-seeking [55].…”
Section: Trace Amine Systemsupporting
confidence: 60%
See 2 more Smart Citations
“…Studies from our lab and others have shown that TAAR1 agonists were effective to attenuate the behavioral and biochemical effects of stimulants such as cocaine and amphetamines [52]. Our recent study also demonstrated that activation of TAAR1 was effective to reduce nicotine-induced dopamine release and neural activation in the NAc [55]. Furthermore, TAAR1 agonists attenuated several kinds of nicotine-related behaviors, e.g., nicotine-induced behavioral sensitization, nicotine discrimination, nicotine self-administration, and reinstatement of nicotine-seeking [55].…”
Section: Trace Amine Systemsupporting
confidence: 60%
“…Our recent study also demonstrated that activation of TAAR1 was effective to reduce nicotine-induced dopamine release and neural activation in the NAc [55]. Furthermore, TAAR1 agonists attenuated several kinds of nicotine-related behaviors, e.g., nicotine-induced behavioral sensitization, nicotine discrimination, nicotine self-administration, and reinstatement of nicotine-seeking [55]. Furthermore, we demonstrated that the dosages of TAAR1 agonists that effectively inhibited addiction-related behaviors had no effect on general motor activity [55].…”
Section: Trace Amine Systemmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, direct infusion of a TAAR1 agonist into the nucleus accumbens also prevented drug-seeking behaviors, whereas TAAR1-KO enhanced nicotine-seeking behaviors. Intriguingly, chronic nicotine administration selectively decreased nucleus accumbens TAAR1 expression (Liu et al, 2018). In this way, chronic nicotine administration may be removing a cellular brake on dopaminergic activity in the central reward centers, thereby promoting its rewarding and addicting properties.…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 99%
“…Administration of TAAR1 agonists was able to decrease nicotine-induced hyperactivity (Liu et al, 2018;Sukhanov et al, 2018), sensitization (Liu et al, 2018;Sukhanov et al, 2018), self-administration (Liu et al, 2018), cue-and drugprimed reinstatement (Liu et al, 2018), and discriminative stimulus effects (Liu et al, 2018), while simultaneously increasing the elasticity of the nicotine demand curve (Liu et al, 2018). These beneficial effects of TAAR1 activation were associated with a decrease in the nicotine-induced dopamine release and c-fos expression in the nucleus accumbens, confirming prevention of hyperactivity of the dopamine reward centers (Liu et al, 2018). Furthermore, direct infusion of a TAAR1 agonist into the nucleus accumbens also prevented drug-seeking behaviors, whereas TAAR1-KO enhanced nicotine-seeking behaviors.…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 99%